PENGARUH PROMOSI INFLUENCER TERHADAP MINAT BELI MASYARAKAT DI KOTA AMBON - Nengsih Stefany Untajana; Marleen Muskita; Rido Latuheru (Jurnal Administrasi Terapan, 2026)
The development of digital technology and social media has introduced influencers as one of the promotional strategies used by MSME actors (Micro, Small, and Medium Enterprises) to influence consumer purchasing behavior. This research aims to determine the influence of influencer promotion on the purchasing interest of Ambon City communities. The research method employed was quantitative with a survey approach. Data were collected through questionnaire distribution to 32 respondents who are social media users in Ambon City. Data analysis was conducted through validity testing, reliability testing, simple linear regression, and hypothesis testing. The research results indicate that influencer promotion has a positive and significant effect on purchasing interest with a t-value of 4.497 > t-table 1.693 at a significance level of 0.00 < 0.05. These findings demonstrate that the better the quality of promotion conducted by influencers, the higher the purchasing interest of consumers. This research is expected to provide beneficial contributions to MSMEs and market practitioners in understanding the role of influencers as an effective promotional strategy in the digital era. Keywords: Influencer, Promotion, Purchase Interest, Social Media, Ambon City